Does Corporate Culture Affect Bank Risk‐Taking? Evidence from Loan‐Level Data. (30th January 2019) - Nguyen, Duc Duy; Nguyen, Linh; Sila, Vathunyoo
Abstract: Using comprehensive corporate and retail loan data, we show that the corporate culture of banks explains their risk‐taking behaviour. Banks whose corporate culture leans towards aggressive competition are associated with riskier lending practices: higher approval rate, lower borrower quality, and fewer covenant requirements. Consequently, these banks incur larger loan losses and make greater contributions to systemic risk. The opposite behaviour is observed among banks whose culture emphasizes control and safety. Our findings cannot be explained by heterogeneity in a bank's business model, CEO compensation incentives or CEO characteristics. We use an exogenous shock to the US banking system during the 1998 Russian default crisis to support a causal inference.